ACTIVLIM‐Hemo: A new self‐reported, unidimensional and linear measure of activity limitations in persons with haemophilia. Issue 1 (12th December 2022) - Lobet, Sébastien; Lambert, Catherine; Foubert, Anthe; Chantrain, Valérie‐Anne; Roussel, Nathalie; Meeus, Mira; Devos, Ann; Maes, Philip; Hermans, Cedric; Penta, Massimo
Abstract: Introduction: To assess activity limitations in people with haemophilia (PwH), the self‐reported Haemophilia Activity List (HAL) is widely employed, despite several methodological limitations impacting the interpretation of categorical scores. Modern psychometric approaches avoid these limitations by using a probabilistic model, such as the Rasch model. The ACTIVLIM is a Rasch‐built measurement of activity limitations previously validated in several clinical conditions like neuromuscular disorders. Aims: This study sought to develop the ACTIVLIM‐Hemo, meaning an ACTIVLIM scale version specifically adapted to assess daily activity limitations in adult PwH. Methods: Daily activities were assessed as "impossible, " "difficult" or "easy" by 114 PwH (median age of 44 years) with 63 of them reassessed after 12 days. The Rasch Rating Scale model was used to identify activities delineating a unidimensional and linear scale unbiased by demographic and clinical status. Concurrent validity was determined through correlation with the HAL sub‐scores and sum score. Results: The ACTIVLIM‐Hemo included 22 pertinent activities, with difficulties independent of demographic and clinical conditions, allowing a reliable measure of activity limitations (PSI = .92) expressed on a linear and unidimensional scale in PwH (7%–100 % range, ceiling effect of 1/114) with excellent test‐retest reliability (ICC = .978). Spearman rank correlations between ACTIVLIM‐Hemo and HAL sub‐scores ranged between .623 and .869. Conclusions: The ACTIVLIM‐Hemo is an easy‐to‐administer, valid and reliable alternative to HAL in assessing activity limitations in PwH. Its invariant scale can be used across conditions and time to compare the functional status of PwH over a wide measurement range. Abstract :